The Effects of Transnational Tourism Corporations On Developing Countries and Less Developed Countries - Radić, Maja Nikšić; Lukinić, Martina (Oeconomica Jadertina, 2017)
The transnational corporations functioning as major carriers and global business factors in today’s globalized environment, are recognizable within the tourism sector through mega hotels, agencies and similar business chains. Foreign hotel chains represent now an established standard that any serious tourist destination must conform to if it is to be competitive within the global tourism market. In view of the importance given to direct foreign investments in tourism, and the expectations of the Croatian government regarding the entry of foreign capital in the tourism sector, the purpose of this paper is to discuss the role and importance of transnational corporations in tourism. The aim of this paper is to synthesize the most important effects of transnational tourism corporations on developing countries and less developed countries.